Development of porous membranes by alkali activation of borosilicate glass: effect of wastewater acidity on copper adsorption - Diana Lago; Jozef Kraxner; Dušan Galusek; Enrico Bernardo (Developments in the Built Environment, 2025)
A highly porous membrane was prepared through weak alkali activation of Duran-type borosilicate glass using a 2.5 M NaOH:KOH solution. The incorporation of fine glass powder (<1 μm) significantly enhances glass network reactivity by increasing the surface area in contact with the alkaline solution. This promotes the dissolution of glass constituents, leading to their subsequent polymerization. Following this process, the material undergoes low-temperature curing at 40 °C, aiding consolidation and stabilization. The resulting porous structure shows excellent performance in copper removal from aqueous media. While adsorption of copper is strongly influenced by the pH of the solution, the adsorption capacity can be adjusted through surface treatment of the activated material. The developed borosilicate-based membranes treated in boiling water can remove between 92 % and 99 % of copper (II) at pH levels 2 and 5, respectively, whereas “raw” alkali-activated samples achieve up to 65 % copper (II) removal at pH 2. These findings underscore the need for tailored strategies to optimize membrane performance across varying pH conditions.